Executable task force pulmonology diseases: bronchial asthma. Copd. Pneumonias. Diagnosis and management approaches - Vizir, V. A.; Berezin, A. E.; Pysanko, O. V.; Візір, Вадим Анатолійович; Березін, Олександр Євгенійович; Писанко, Оксана Володимирiвна (Zaporozhye state medical university, 2017)
Executable task force is addressed to students of 5th courses of medical university for helping to study of internal medicine according pulmonology diseases.